The Issues of Residential House Systems and How to Make It More Sustainable Systems - Ahmad, Ahmad R. (Academic Journal of Nawroz University, 2020)
This paper highlighted a set of issues facing the residential house system and makes it unsustainable systems including: high energy consumption, high water demand, waste generation, and carbon dioxide emissions. The boundaries, inputs and outputs of residential house systems are displayed in detail and illustrated by modeling these systems for the purpose of understanding the relationships and interactions between these inputs and outputs and components of these systems. Thus, presenting a range of strategies that can be implemented to make residential house systems more sustainable and reduce the negative impacts of these systems on the environment and other sources such as water, energy and non-renewable resources to a minimum level.